Activation of renal epithelial Na+ channels (ENaC) in infants with congenital heart disease - Ortmann, Laura A.; Nandi, Shyam; Li, Yu-long; Zheng, Hong; Patel, Kaushik P. (Frontiers in Pediatrics, 2024)
 Proteases known to activate ENaC were elevated in infants with congenital heart disease compared to healthy infants and their urine produced a significantly greater increase in Na + inward currents in cortical collecting duct cells. There was no further increase in urinary proteases after cardiac surgery and protease levels were not associated with post-operative fluid overload. ENaC activate could be a contributor to pre-operative fluid retention in children with unrepaired congenital heart disease.